Mad men carousel the complete critical companion - Seitz, Matt Zoller 1968- (Abrams, 2015)
"This book is a time machine. It goes backwards and forwards through all seven seasons. It takes longtime fans to a place where they ache to go again. It guides new viewers on their first trip to 1960s Madison Avenue. It lets us think about the show the way a TV critic does. Around and around and back home again, to a place where we know why it's loved."--Jacket
Keywords: Mad Men; Mad men (Television program) / Criticism and interpretation; Mad men (Television program); Mad men (US, 2007-); Nineteen sixties; Civilization; Manners and customs; TV-serier, USA.; Alltag, Brauchtum; United States / Social life and customs / 1945-1970; United States / Civilization / 1945-; United States; USA